Reaction Time Analysis On Female Workers with a Night Shift Work System at A Textile Factory in Sumedang: a Quasi-Experimental Study - Suratna, Sang Ketut; Jen Fuk, Liem; Kusumadewi, Dian (UI Scholars Hub, 2023)
Abstract Introduction. Shift work is a common work system in textile factories. The shift system affects workers’ diet and nutritional needs. Malnutrition has a high potential in causing fatigue. Thus, additional food recommendations and nutritional education for this population are needed. Linear Programming (LP) can be used to create a Food Based Recommendation (FBR) for textile industry owners who employ female workers with a shift system. Local food ingredients can be used to optimize nutritional content. Objective. To analyze the effect of additional food recommendations on reaction time in female night shift workers. Methods. This study analyzed the diet and reaction time of 100 female workers in Rancaekek, Sumedang Regency using a quasi-experimental design. The data was combined with 24-hour food recall and 5 FFQ (5-days food-frequency questionnaire). Reaction time was evaluated using lakassidaya. LP uses the Optifood system to formulate a Food-Based Recommendation (FBR). Results. The difference in reaction time between pre-and post-intervention in the intervention group was 12.97 milliseconds (p = 0.006), while the difference in reaction time between the combined group was 8.18 milliseconds (p = 0.007). Conclusion. Adequate energy intake through recommended FBR was effective in reducing reaction time. Recommendations for additional food menus and nutrition education can be used by workers and company owners.